Comparison of HbA1c detection in whole blood and dried blood spots using an automated ion-exchange HPLC system. (March 2017) - Maleska, Aleksandra; Hirtz, Christophe; Casteleyn, Elise; Villard, Orianne; Ducos, Jacques; Avignon, Antoine; Sultan, Ariane; Lehmann, Sylvain
Aim: Hemoglobin A1c (HbA1c) is a widely recognized analyte for diagnosing and monitoring diabetes. Dried blood spot (DBS) constitutes a useful alternative to blood collection by venipuncture. Analytical and clinical validation of DBS use is, however, necessary before implementation.Results/methodology: HbA1c levels from whole blood or DBS from a cohort patients with diabetes were compared. DBS specimens were stable at ambient temperature. HbA1c detection on DBS was accurate, robust, and the correlation and agreement with whole blood values was excellent.Conclusion: This study provides for the first time a complete method comparison and validation under the ISO15189 guideline using an automated HPLC system. This approach constitutes, therefore, a useful tool for diagnosing diabetes.